Understanding Knowledgeable Workers’ Behavior Toward COVID-19 Information Sharing Through WhatsApp in Pakistan - Islam, Talat; Mahmood, Khalid; Sadiq, Misbah; Usman, Bushra; Yousaf, Sheikh Usman (Frontiers in Psychology, 2020)
Using social media through mobile has become a major source of disseminating information; however, the motivations that impact social media users’ intention and actual information-sharing behavior need further examination. To this backdrop, drawing on the uses and gratifications theory, theory of prosocial behavior, and theory of planned behavior, we aim to examine various motivations toward information-sharing behaviors in a specific context [coronavirus disease 2019 (COVID-19)]. We collected data from 388 knowledgeable workers through Google Forms and applied structural equation modeling to test the hypotheses. We noted that individuals behave seriously toward crisis-related information, as they share COVID-19 information on WhatsApp not only to be entertained and seek status or information but also to help others. Further, we noted norms of reciprocation, habitual diversion, and socialization as motivators that augment WhatsApp users’ positive attitude toward COVID-19 information-sharing behavior.